Pengaruh Brand Awareness Dan Brand Trust Terhadap Pengambilan Keputusan Pembelian Produk Mie Instan Indomie Di Kota Langsa - Fitriya, Nur; Indah, Dewi Rosa; Safrizal, Safrizal (Universitas Labuhanbatu, 2022)
This study aims to determine1 the effect of brand awareness and brand trust on purchasing decisions of Indomie instant noodle products in Langsa City. The sample in this study amounted to 96 respondents. The data analysis method used multiple linear regression analysis with the regression equation, namely Y = 5.199 + 0.150X1 + 0.751X2 + 0.310X3. From the t test, it is known that brand awareness and brand trust partially have a significant effect on purchasing decisions for Indomie instant noodle products in Langsa City. From the F test, it is known that brand awareness and brand trust simultaneously have a significant effect on purchasing decisions for Indomie instant noodle products in Langsa City. Brand awareness and brand trust affect the purchase decision of Indomie instant noodle products in Langsa City by 58.6%, while the remaining 41.4% is influenced by other variables outside this research model.